2003
DOI: 10.1074/jbc.m209395200
|View full text |Cite
|
Sign up to set email alerts
|

3-Mercaptopyruvate Sulfurtransferase of LeishmaniaContains an Unusual C-terminal Extension and Is Involved in Thioredoxin and Antioxidant Metabolism

Abstract: Cytosolic 3-mercaptopyruvate sulfurtransferases (EC 2.8.1.2) of Leishmania major and Leishmania mexicana have been cloned, expressed as active enzymes in Escherichia coli, and characterized. The leishmanial singlecopy genes predict a sulfurtransferase that is structurally peculiar in possessing a C-terminal domain of some 70 amino acids. Homologous genes of Trypanosoma cruzi and Trypanosoma brucei encode enzymes with a similar C-terminal domain, suggesting that this feature, not known in any other sulfurtransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
87
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 50 publications
(51 reference statements)
3
87
0
Order By: Relevance
“…However, it has been reported that MST can both oxidize thioredoxin, a key intermediate in cellular redox reactions, and react with peroxides and that this may be a physiologically significant mechanism for combating oxidative challenges [41,42]. Recently, it has been reported that overexpression of ALDH-2 confers lung epithelial cell resistance to hyperoxia-induced cell death in part by reducing intracellular and mitochondrialderived ROS production [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that MST can both oxidize thioredoxin, a key intermediate in cellular redox reactions, and react with peroxides and that this may be a physiologically significant mechanism for combating oxidative challenges [41,42]. Recently, it has been reported that overexpression of ALDH-2 confers lung epithelial cell resistance to hyperoxia-induced cell death in part by reducing intracellular and mitochondrialderived ROS production [43].…”
Section: Discussionmentioning
confidence: 99%
“…This domain does not share homology with any known proteins in the available databases. The presence of an unusual polypeptide extension has also been found in the subunit II of RNA polymerase I of T. brucei and L. major, which harbor an N-terminal 250 amino acid extension (40,41), and the 3-mercaptopyruvate sulfur-transferase enzymes of L. major and Leishmania mexicana, which contain 70 additional amino acids at their C terminus (42). So far no function could be assigned to these domains.…”
Section: Discussionmentioning
confidence: 99%
“…The TUM1-bound persulfide can be transferred to acceptors such as cyanide to generate the less toxic thiocyanate (44). Alternatively, H 2 S can be released from TUM1 in the presence of reducing systems like thioredoxin or glutathione (45,46). Inhibition of TUM1 conserves cysteine and contributes to an increase in the cysteine pool (47,48).…”
Section: Discussionmentioning
confidence: 99%